2021
DOI: 10.1128/msystems.00622-21
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Vulvovaginal Candidiasis: a Dynamic Interkingdom Biofilm Disease of Candida and Lactobacillus

Abstract: RVVC is a significant burden, both economically and for women's health, but its prevalence is poorly documented globally due to the levels of self-treatment. Identifying triggers for development and recurrence of VVC and the pathogenesis of the microbes involved could considerably improve prevention and treatment options for women with recurrent, azole-resistant cases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…In addition, it is well known that Candida species, mainly C. albicans, can form thick and tough biofilms, which greatly increases the tolerance to antifungal drugs during the treatment of recurrent vulvovaginal candidiasis (Taff et al, 2013). Mckloud et al reported the ability of various Lactobacillus species to inhibit C. albicans biofilm formation and biofilm-related gene expression when cocultured (McKloud et al, 2021). Lactobacillus rhamnosus could down-regulate C. albicans biofilm-related gene expression.…”
Section: Iners and Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is well known that Candida species, mainly C. albicans, can form thick and tough biofilms, which greatly increases the tolerance to antifungal drugs during the treatment of recurrent vulvovaginal candidiasis (Taff et al, 2013). Mckloud et al reported the ability of various Lactobacillus species to inhibit C. albicans biofilm formation and biofilm-related gene expression when cocultured (McKloud et al, 2021). Lactobacillus rhamnosus could down-regulate C. albicans biofilm-related gene expression.…”
Section: Iners and Biofilm Formationmentioning
confidence: 99%
“…Mckloud et al. reported the ability of various Lactobacillus species to inhibit C. albicans biofilm formation and biofilm-related gene expression when cocultured ( McKloud et al., 2021 ). Lactobacillus rhamnosus could down-regulate C. albicans biofilm-related gene expression.…”
Section: Iners and Women Diseasesmentioning
confidence: 99%
“…More specifically, there is a particular interest in characterizing the complex interactions that may occur between Candida yeasts, bacterial communities of the microflora, and epithelial and immune cells residing in the vaginal mucosa, because this knowledge could help in developing new strategies for early diagnoses and better targeting of antifungal therapeutic interventions ( 4 ). As such, the study led by the Gordon Ramage research group and recently published in mSystems provides an unprecedented insight into the fluctuations in antagonistic interkingdom interactions between Candida and Lactobacillus associated with RVVC disease ( 5 ) ( Fig. 1 ).…”
Section: Commentarymentioning
confidence: 99%
“…Pathobiology consists of a strong inflammation of the mucosa at the origin of typical symptoms such as burning, itching, white clumpy discharge, and redness of the genital track. McKloud and colleagues ( 5 ) provide unprecedented insight into the complex microbial interplay underlying RVVC. Notably, they show that the bacterium Lactobacillus crispatus is able to condition a healthy vaginal environment by reducing Candida albicans load.…”
Section: Commentarymentioning
confidence: 99%
“…Several studies have proposed that biofilm formation by C. albicans plays a crucial role in the development of vaginal candidiasis [11][12][13][14][15]. Wu et al [16] supported the essential role of biofilm formation in the pathogenesis of vaginal candidiasis, demonstrating that histological damages of mucosal epithelial cells and local inflammation are associated with biofilm growth on the vaginal epithelium.…”
Section: Introductionmentioning
confidence: 99%